Highly chemo- and regioselective synthesis and subsequent directional catalyst-free transformation of enantiopure bioxirane derivatives. (7th May 2022) - Hu, Xiaoyun; Li, Kang; Guo, Jianxin; Wang, Cui; Ma, Ling; Borovkov, Victor
Abstract: A novel and practical method for the synthesis of (2 S, 2 ′S )-3, 3, 3′, 3′-tetraaryl-2, 2′-bioxiranes from natural tartaric acid has been developed. Four-step synthetic protocol includes the following steps: esterification of tartaric acid, arylation of tartaric esters, highly regioselective 2, 3-cyclosulfitation, 1, 4-chlorination of (2 R, 3 R )-1, 1, 4, 4-tetraarylbutanetetraols with thionyl chloride, and intramolecular cyclization reaction. It was confirmed that no stereochemical inversion of the chirogenic centers upon preparation of bioxirane derivatives takes place. Further methodology of the catalyst-free regiospecific transformation to enantiopure 1, 3-oxazoline-2-thione derivatives has successfully been developed by coupling the bioxiranes with NH4 SCN, which provides a new and facile access to different TADDOL derivatives. Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Image 1